How CEO Social Media Disclosure and Gender Affect Perceived CEO Attributes, Relationship Investment, and Engagement Intention. (December 2021) - Yue, Cen April; Chung, Yoo Jin; Kelleher, Tom; Bradshaw, Amanda S.; Ferguson, Mary Ann
How does a chief executive officer (CEO)'s social media content disclosure on Twitter affect perceived CEO attributes, relationship investment, and public engagement, and to what extent does the CEO's gender (male vs. female) moderate how publics evaluate content disclosures? A 2 (CEO gender: male vs. female) × 4 (level of disclosure: 100% corporate vs. 70% corporate and 30% personal vs. 30% corporate and 70% personal vs. 100% personal disclosure) between-subject experimental design was used to address these questions with a random sample of 465 adult Twitter users in the United States. Results showed that posts that featured high personal disclosure did not increase the perceived likability or competence of the CEO. Nor did CEO gender impact these outcomes. However, CEO professional disclosure proved to be an effective means to gain high levels of perceived relationship investment from publics. Finally, publics may hold implicit gender bias in cognitive (i.e., perceived relationship investment) and behavioral evaluation (i.e., engagement intention) of a female CEO.